Optimal Decision-making Method of Wind-proof and Disaster-resistant Reinforcement Measures for Distribution Network - Xin GAO; Fei TANG; Tongyan ZHANG; Yu LI (发电技术)
Typhoon is one of the common natural disasters, which will seriously affect the normal operation of the distribution network infrastructure. Reinforcing system infrastructure (such as wires and poles) to improve their disaster resilience is an effective way to reduce losses caused by extreme weather events. Therefore, this paper proposes a pre-disaster reinforcement strategy for the distribution network infrastructure considering economic constraints. Firstly, the models of occurrence of extreme weather, component fragility and the disaster response process were created. Then, the disaster resilience of distribution network was evaluated via Monte Carlo simulation. The reinforcement strategy was further optimized through the particle swarm optimization algorithm, considering the total reinforcement budget, the load importance and the component fragility. Finally, the proposed strategy was applied to an improved 18-bus distribution system to verify its effectiveness.